Personal Branding of Haji Muhidin in Building Political Communication on Instagram Social Media - Hayat, Muzahid Akbar; Wahyuni, Linda; Saputra, Muhammad Irwan; Hayati, Nisrina Rahmah; Sari, Ema Purnama (UNIVERSITAS PAKUAN, 2024)
The role of social media, particularly Instagram, in political communication has become a phenomenon that attracts significant attention. As one of the most popular forms of mass media, social media offers a more effective and efficient way to convey information. Instagram plays a crucial role in building the personal branding of politicians, helping them introduce themselves, create a positive image, present their background, and affirm their political identity.This study aims to discuss how the Instagram account @HajiMuhidin builds political communication using the personal branding pyramid strategy. Through a targeted content strategy, Haji Muhidin has successfully conveyed relevant and engaging political messages to his followers. The research employs a descriptive qualitative method, aiming to analyze the phenomenon in detail and descriptively concerning the research subject. The findings of this study highlight the importance of social media in the modern political landscape, where effective communication can influence public perception and build trust. Haji Muhidin’s success in establishing personal branding is reflected in his image as a candidate for governor of South Kalimantan who is characterized by integrity, friendliness, intelligence, culture, and religiosity. This image can be observed through the support expressed by the community in the comments section of Instagram posts on @hajimuhidinpan. This research is expected to contribute to the development of more effective communication strategies.